Municipality Declaration, Urban Imagination and Urban Experience A Case of Putalibazaar and Walling, Syangja, Nepal - Bhandari, Amrit Kumar (Himalayan Journal of Sociology and Anthropology, 2014)
Municipalities, which are basically administrative divisions, have been treated as urban entities in Nepal, though most of them lack even the basic urban amenities. Municipality declaration by government can be taken as an effort to foster the process of urbanization in Nepal. On the basis of firsthand qualitative data collected through interviews, observations and focused group discussions conducted in the two municipalities: Putalibazaar and Walling of Syangja District of Western Nepal, this article attempts to highlight the status of urbanization here after 17 years of municipality declaration. This article reveals that local people were out of sorts about how urbanization flourishes in their area due to municipality declaration. It also divulges that local people themselves, municipality offices and other governmental and non-governmental agencies have not been able to make vibrant contribution in the urbanization process. Therefore, this article concludes that the mere act of municipality declaration cannot foster urbanization; thus local people and municipalities offices need to play collective, more responsible, productive and meaningful role to transform the urban imagination into a reality. DOI: http://dx.doi.org/10.3126/hjsa.v6i0.10686 Himalayan Journal of Sociology and Anthropology Vol.6 2014: 1-21